Tuning the magnetic and dielectric properties of Fe3O4 nanoparticles for EMI shielding applications by doping a small amount of Ni2+/Zn2+. (March 2023) - Rehman, Atta Ur; Atif, M.; Rehman, Ubaid ur; Wahab, H.; Ling, Francis Chi-Chung; Khalid, W.; Ul-Hamid, A.; Ali, Z.; Nadeem, M.
Abstract: Magnetite ( Fe 3 O 4 ) nanoparticles have been considered as a promising microwave absorption materials. To further tune their electromagnetic interference shielding efficiency, different compositions of doped Ni 0.01 − x Zn x Fe 2.99 O 4 ( x  = 0.0, 0.005, 0.01) nanoparticles were synthesized by the co-precipitation technique. The prepared nanoparticles structure was characterized by X-ray diffraction, transmission electron microscopy, and Mössbauer spectroscopy. Impedance spectroscopy and magnetic measurements showed a dramatic enhancement in the dielectric and magnetic properties of Ni 2 + doped Fe 3 O 4 among the prepared samples, respectively. This is ascribed to the homogeneous distributed microstructure and considerable Fe 2 + / Fe 3 + ratio at the octahedral sites due to unusual cation redistribution in the Ni 0.01 Fe 2.99 O 4 nanoparticles. Moreover, the measurements of total shielding efficiency exhibited an improvement of 83% in the shielding effectiveness of Ni 0.01 Fe 2.99 O 4 (∼22 dB) with the absorption dominant mechanism compared to pure Fe 3 O 4 (∼12 dB) in the X-band frequency range. This is probably the result of a better impedance matching between the permittivity/permeability and dielectric/magnetic losses. Graphical Abstract: ga1 Highlights: The magnetic/dielectric properties of Fe 3 O 4 are tuned by small doping of Ni 2 + / Zn 2 + . The 1.0 wt% Ni 2 + doping has the maximum M s, colossal permittivity, and reduced tan δ . Ni 0.01 Fe 2.99 O 4 sample improves SE T by 83% via an absorption-dominant mechanism. Shielding properties depend on the synergy between magnetic/dielectric parameters.